Application of adjusted indirect comparisons to assess bioequivalence and switchability between generic drugs – example of clopidogrel - Pejčić, Zorica; Vučićević, Katarina; García-Arieta, Alfredo; Miljković, Branislava (Archives of Pharmacy, 2022)
Generic medicines are bioequivalent (BE) and switchable with the reference medicine, however, between generics BE is not demonstrated. In practice, patients are often offered generic substitution, where information on BE between generics may be useful, especially when there is a doubt that substitution may potentially pose a risk to the patient. These information can be obtained by assessing BE between generics, applying the method of adjusted indirect comparison (AIC). This method is based on data from BE studies in which generics were compared with the same reference medicine. Thus, it is possible to identify generics for which efficacy and safety problems are not expected upon substitution (1,2). The AIC was used to compare four generic clopidogrel medicines. Publicly available data from original BE studies, in which each generic medicine was compared with the reference medicine Plavix film-coated tablets 75 mg, were analysed. Generics were considered BE if the 90% confidence interval (CI) for the ratio of their pharmacokinetic parameters maximum plasma concentration (Cmax) and area under the curve up to the last measurable concentration (PIK0-t), was within the acceptance range 80.00-125.00%. In all the tested combinations, 90% CIs for PIK0-t were within the acceptance range, while for Cmax 90% CIs were within or very close to the limits, with the point estimate being within the range in all cases. The results obtained by the AIC indicated that the bioavailability of these four generic clopidogrel medicines is very similar, therefore they can be considered switchable with each other in clinical practice.